Preliminary techno-economic and environmental assessment of thickness dependent physical aging in oxygen enriched combustion using polymeric membranes - Lock, S.S.M. (Elsevier Ltd, 2017)
Current study is a pioneering work to demonstrate the methodology and vitality to incorporate physical aging effect in process simulation, economic study and environmental assessment of polymeric membranes under varying thicknesses (25–500 nm) applied in O2 enriched combustion. In this work, the volume relaxation in polymeric membrane during aging has been modelled employing the dual mode mechanism (e.g. Lattice contraction and free volume diffusion) in finite element numerical solution. Later, the dual mode model has been integrated within a succession of states methodology that analytically addresses the separation mechanism of membrane according to the solution-diffusion equation. Finally, the model has been included in Aspen HYSYS process simulator as a membrane unit operation extension to constitute the entire process flow in a combustion plant. Accuracy of the simulation model has been validated with laboratory data (error <5). It is found that the thinner polymeric membrane is the more economical option, whereby internal rate of return (IRR) can be increased from 2.91 to 82.91 when polymeric membrane thickness is reduced from 500 nm to 25 nm. In addition, incorporation of physical aging mechanism is particularly important in thinner membrane structure, whereby percentage IRR deviation can reach 8.18 for 25 nm thick films. © 2017 Elsevier Ltd